2007
DOI: 10.1196/annals.1395.037
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Dependent Effects on Functional Aspects in Human Satellite Cells

Abstract: In humans aging is a complex process that determines many physical and metabolic alterations correlated to the accumulation of oxidative damage in different tissues. Sarcopenia is an age-related nonpathological condition that includes a progressive loss of mass and strength in skeletal muscle, associated with a decline in the fibers' functional capability. This condition could be correlated to abnormal reactive oxygen species (ROS) accumulation with consequent fiber oxidative damage. This complex situation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 15 publications
7
44
0
1
Order By: Relevance
“…The increase in membrane lipid peroxidation (Beccafico et al, 2007) related to alterations in antioxidant enzyme activities (GPX and GST) (Fanò et al, 2001), reported previously by our group, was confirmed by the transcriptional profile reported in this study showing alterations in the expression patterns of genes encoding antioxidant enzymes. This condition leads to increased membrane rigidity (Fulle et al, 2005), and together with other factors, may be responsible for insufficient ability to fuse into myotubes noted during in vitro myogenesis of elderly satellite cells.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The increase in membrane lipid peroxidation (Beccafico et al, 2007) related to alterations in antioxidant enzyme activities (GPX and GST) (Fanò et al, 2001), reported previously by our group, was confirmed by the transcriptional profile reported in this study showing alterations in the expression patterns of genes encoding antioxidant enzymes. This condition leads to increased membrane rigidity (Fulle et al, 2005), and together with other factors, may be responsible for insufficient ability to fuse into myotubes noted during in vitro myogenesis of elderly satellite cells.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, MMP1 is involved in specific protein substrate digestion of the extracellular matrix, and is fundamental in facilitating cellular migration when myocytes fuse and form myotubes (Saffarian et al, 2004). These results are consistent with the increase in membrane rigidity in myotubes of the elderly (Fulle et al, 2005) that may be attributed to enhanced lipid peroxidation (Beccafico et al, 2007), increasing the difficulty of migration and fusion. Therefore, the lower motility of senescent myoblasts and myotubes, 17 also observed by other investigators (Renault et al, 2000), may be attributed to increase in extracellular matrix deposition.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations